THE IMPACT OF EMERGING TECHNOLOGIES OF THE FOURTH INDUSTRIAL REVOLUTION ON THE QUALITY OF ACCOUNTING DISCLOSURE IN FINANCIAL REPORTS: A FIELD STUDY ON A SAMPLE OF IRAQI PRIVATE BANKS LISTED IN THE IRAQ STOCK EXCHANGE - Ammar Taha Yassin; Samir Emad Shaaban; Basim Rashid Ali (Scholars Digest Publishing, 2024)
The research aimed to study and analyze the impact of Fourth Industrial Revolution technologies on the quality of accounting disclosure through the information disclosed by Iraqi banks in their published financial reports, And learn about the most important of these emerging technologies that work to improve the level of disclosure in published financial reports, which contributes to providing opportunities for competition in the stock market. This is done by applying it to a sample of Iraqi private banks. The descriptive analytical approach was adopted and the questionnaire was used as a tool for the study. While the study found a significant effect between the emerging technologies of the Fourth Industrial Revolution and the quality of accounting disclosure at a significance level of (0.01). The study recommended the need to increase awareness among bank managements of the importance of applying these technologies through diversity, volume and speed of data processing, keeping pace with technological progress and the ability to compete in the stock market.
Keywords: Emerging technologies, accounting disclosure quality, financial reports, commercial banks.